Informasi Citra Anatomi CT Scan Kepala pada Kasus Stroke Iskemik dengan Variasi Windowing - Putro, Wahyu Murti Cahyo; Sulaksono, Nanang; Wibowo, Ardi Soesilo (Poltekkes Kemenkes Semarang, 2025)
Background: Ischemic stroke is a critical condition detectable through head CT scans, where windowing techniques significantly enhance brain tissue visualization. At Bethesda Hospital Yogyakarta, differing windowing protocols are used in the Emergency and Main Radiology Departments, yet no standardized stroke-specific window has been established. This study aims to identify the differences in anatomical information in head CT scans with various windowing settings and to determine the most optimal windowing protocol.Methods: This research is a quantitative-experimental study conducted at Bethesda Hospital Yogyakarta involving 10 patients with ischemic stroke, using variations of windowing settings: WW 120 HU WL 60 HU, WW 100 HU WL 35 HU, and WW 40 HU WL 40 HU. The image results were evaluated by two respondents based on the anatomical information of brain parenchyma, insular cortex, internal capsule, left and right cerebral hemispheres, and brain sulci. The data analysis was performed using the Friedman statistical test.Results: The results of the study showed that the WW 100 HU WL 35 HU setting provided the most informative anatomical visualization across all evaluated brain structures. In contrast, WW 120 HU WL 60 HU was the least informative for the brain parenchyma and insular cortex, while WW 40 HU WL 40 HU offered moderate clarity for most structures but was suboptimal for the brain parenchyma. These differences were confirmed by the Friedman test, with a p-value 0.05.Conclusions: There were differences in anatomical information across the various windowing settings in head CT scan examinations for ischemic stroke cases. In addition, the highest overall and individual anatomical mean rank was found in the WW 100 HU WL 35 HU windowing setting, with a value of 2.95.